Mitogen-activated Protein Kinase 7 Promotes Cell Proliferation, Migration and Invasion in SOSP-M Human Osteosarcoma Cell Line. Issue 5 (September 2017) - Huang, Yan; Yao, Jianhua; Zhu, Bing; Zhang, Jianzheng; Sun, Tiansheng
Purpose: Osteosarcoma (OS) is the most common primary bone tumor and has low cure rates. Our study aimed to evaluate the roles of mitogen-activated protein kinase 7 (MAPK7) in cell proliferation, migration and invasion using the SOSP-M human OS cell line as an in vitro model. Methods: SOSP-M cells were transfected with PCDNA3.1-MAPK7 and siRNA-MAPK7 plasmids using Lipofectamine 2000. Quantitative real-time polymerase chain reaction (RT-PCR) was performed to determine the relative expression level of MAPK7 and Western blot analysis was carried out to determine the expression level of ERK5 protein. Then MTT, scratch wound healing and Matrigel transwell assays were used to investigate the roles of MAPK7 expression in the proliferation, migration and invasion, respectively, of SOSP-M cells in vitro . Results: RT-PCR analysis showed that the expression level of MAPK7 increased significantly after transfection with PCDNA3.1-MAPK7 plasmid compared with the blank group, while it decreased significantly after transfection with siRNA-MAPK7 plasmid. Similar results for ERK5 expression were obtained by Western blot analysis. In addition, the cell proliferation rate, cell migration rate and invasive cell number in the PCDNA3.1-MAPK7 transfection group increased significantly compared with the blank group, while they decreased significantly in the siRNA-MAPK7 transfection group. Conclusions: Our results indicate that overexpression of MAPK7 in human OS cells could promote cell proliferation, migration and invasion, whereas knockdown of MAPK7 expression had the opposite effect. All the results suggest that MAPK7 may serve as a potent target for drug development.